2015
DOI: 10.1038/srep14630
|View full text |Cite
|
Sign up to set email alerts
|

Development of ‘Redox Arrays’ for identifying novel glutathionylated proteins in the secretome

Abstract: Proteomics techniques for analysing the redox status of individual proteins in complex mixtures tend to identify the same proteins due to their high abundance. We describe here an array-based technique to identify proteins undergoing glutathionylation and apply it to the secretome and the proteome of human monocytic cells. The method is based on incorporation of biotinylated glutathione (GSH) into proteins, which can then be identified following binding to a 1000-protein antibody array. We thus identify 38 sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Glutathione and S-transferases are also important for the S-glutathionylation of a number of proteins with cysteine residues (35,36). Two common target proteins of S-glutathionylation are keratins and actin (22,37). EO cells from Stim1/2 K14cre mice showed a substantial downregulation of keratins and decreased development of tonofibrils, consistent with altered glutathione system.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Glutathione and S-transferases are also important for the S-glutathionylation of a number of proteins with cysteine residues (35,36). Two common target proteins of S-glutathionylation are keratins and actin (22,37). EO cells from Stim1/2 K14cre mice showed a substantial downregulation of keratins and decreased development of tonofibrils, consistent with altered glutathione system.…”
Section: Discussionmentioning
confidence: 91%
“…Changes in the glutathione system had a broader effect. For example, keratins, which serve as a part of the ameloblast's cytoskeleton forming tonofilaments (tonofibrils) (21), are known to undergo S-glutathionylation (22), which can have an effect in ameloblast morphology. RNAseq data showed that mRNA expression of many keratin genes was significantly downregulated in Stim1/2-deficient ameloblasts, including Krt4, Krt13, Krt16, Krt19, and Krt27 (Supplemental Figure 4, A and B).…”
Section: Loss Of Stim1 and Stim2 Causes Minor Changes In Enamel Gene mentioning
confidence: 99%
“…Large-scale proteomic studies have identified numerous redox-sensitive proteins including some extracellular proteins. For instance, two recent elegant studies identified a set of glutathionylated proteins released during inflammation (Checconi et al, 2015; Mullen et al, 2015). Nevertheless, likely due to the extremely low levels of production, none of the cytokines (including IL-1β) were identified as glutathionylation targets in the previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-peer-review manuscript 27 In the context of oxidative stress, several redox proteomics techniques and their application to the field of inflammation and neuroinflammation have led to the identification of specific oxidized proteins undergoing carbonylation (149) or glutathionylation (26,103). The extension of omics to oxidative post-translational modifications may add a dimension to the information obtained and eventually provide a more precise way of identifying exposure to agents that cause oxidative stress.…”
Section: Exposome and Adverse Outcome Pathways: Inflammation And Ros mentioning
confidence: 99%